Microstructure of the Distal Radius and Its Relevance to Distal Radius Fractures - Bain, Gregory Ian; MacLean, Simon Bruce Murdoch; McNaughton, Tom; Williams, Ruth (Journal of Wrist Surgery, 2017)
Background There is a paucity of information on the microstructure of the distal radius, and how this relates to its morphology and function.Purpose This study aims to assess the microanatomical structure of the distal radius, and relate this to its morphology, function, and modes of failure.Methods Six dry adult skeletal distal radii were examined with microcomputed tomography scan and analyzed with specialist computer software. From 3D and 2D images, the subchondral, cortical, and medullary trabecular were assessed and interpreted based on the overall morphology of the radius.Results The expanded distal radial metaphysis provides a wide articular surface for distributing the articular load. The extrinsic wrist ligaments are positioned around the articular perimeter, except on the dorsal radial corner. The subchondral bone plate is a 2 mm multilaminar lattice structure, which is thicker below the areas of the maximal articular load. There are spherical voids distally, which become ovoid proximally, which assist in absorbing articular impact. It does not have Haversian canals. From the volar aspect of the lunate facet, there are thick trabecular columns that insert into the volar cortex of the radius at the metaphyseal–diaphyseal junction. For the remainder of the subchondral bone plate, there is an intermediate trabecular network, which transmits the load to the intermediate trabeculae and then to the trabecular arches. The arches pass proximally and coalesce with the ridges of the diaphyseal cortex.Conclusion The distal radius morphology is similar to an arch bridge. The subchondral bone plate resembles the smooth deck of the bridge that interacts with the mobile load. The load is transmitted to the rim, intermediate struts, and arches. The metaphyseal arches allow the joint loading forces to be transmitted proximally and laterally, providing compression at all levels and avoiding tension. The arches have a natural ability to absorb the impact which protects the articular surface. The distal radius absorbs and transmits the articular impact to the medullary cortex and intermediate trabeculae. The medullary arches are positioned to transmit the load from the intermediate trabeculae to the diaphysis.Clinical Relevance The microstructure of the distal radius is likely to be important for physiological loading of the radius. The subchondral bone plate is a unique structure that is different to the cancellous and cortical bone. All three bone types have different functions. The unique morphology and microstructure of the distal radius allow it to transmit load and protect the articular cartilage.
Keywords: distal radius; fracture; ultrastructure; microarchitecture; micro-CT